Effects of GFF Bands on Normal and High Strength Concrete Cylinders - Jayaprakash, J.; Abdul Samad, Abdul Aziz; Mohamad, Noridah; Choong, K.K.; Megat Azmi, M.J.; Badorul, H.A.B. (International Journal of Integrated Engineering, 2010)
This paper exemplifies the effects of externally confined Glass Fibre Fabric (GFF) bands onnormal and high strength concrete cylinders. Twelve normal and high strength concretecylinders were cast and tested in the laboratory environment under axial compression tofailure. The experimental results show that the degree of confinement of discrete GFFconfined high strength concrete cylinders was significantly better than normal strengthconcrete cylinders with GFF bands, however the ductility of GFF confined high strengthconcrete cylinders was relatively less than GFF normal strength concrete. It was also foundthat the application of horizontally oriented GFF bands is the most effective confining patternthan spirally oriented GFF bands.